Meningkatkan kemampuan membaca permulaan dengan pendekatan quantum learning berbantuan aplikasi Canva pada siswa kelas II - Popong Hoerun Nisa; Ryan Dwi Puspita; Yeni Hadianti (IKIP Siliwangi, 2024)
This study aimed to investigate the effectiveness of the quantum learning model assisted by Canva application in improving the early reading skills of grade 2 students. The use of this model was based on the problem of low motivation, interest, and less engaging learning activities. This research employed a quantitative descriptive method with a one-group pretest-posttest design. The sample consisted of 22 grade 2 students at SDN Cibeber 3, Cimahi City. Data analysis was conducted using a paired sample t-test, normalized gain (N-Gain) test, and a questionnaire to assess students' responses after following this learning model. The results showed that: 1) There was a significant increase in students' early reading skills after following the quantum learning model assisted by Canva application; 2) The N-gain score of 0.46 or 46% was categorized as less than effective; 3) Further development and efforts are needed to improve the effectiveness of using the quantum learning model; and 4) The results of the student questionnaire indicated that the illustrations on the learning texts helped students become more enthusiastic during the learning process.